2019
DOI: 10.3928/02793695-20190225-01
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Perceived Nurse Caring and Patient Satisfaction in Patients in a Psychiatric Acute Care Setting

Abstract: Patients admitted to psychiatric acute care settings benefit from interactions and caring relationships with hospital staff. The current study describes the association between patients' perceptions of nurse caring and their satisfaction with care at an inpatient psychiatric–mental health unit. The relationship between patients' perceptions of nurse caring and two measures of satisfaction with care were explored. A convenience sample of patients ( N = 169) completed the Caring Behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…Most participants in this study were satisfied with their last interaction with staff, in line with previous quantitative studies suggesting that patient generally tend to be satisfied with PIC (Kuosmanen et al, 2006;Ratner et al, 2018). Previous studies have shown that the characteristics of healthcare staff that contribute most to satisfaction with care are respect, caring, and kindness (H€ orberg et al, 2004;King et al, 2019;Wagoro et al, 2008) and that patients are generally satisfied with their relationships with healthcare staff (Wagoro et al, 2008). This is in line with our findings, showing that most participants perceived their healthcare staff as both competent and compassionate.…”
Section: Discussionsupporting
confidence: 87%
“…Most participants in this study were satisfied with their last interaction with staff, in line with previous quantitative studies suggesting that patient generally tend to be satisfied with PIC (Kuosmanen et al, 2006;Ratner et al, 2018). Previous studies have shown that the characteristics of healthcare staff that contribute most to satisfaction with care are respect, caring, and kindness (H€ orberg et al, 2004;King et al, 2019;Wagoro et al, 2008) and that patients are generally satisfied with their relationships with healthcare staff (Wagoro et al, 2008). This is in line with our findings, showing that most participants perceived their healthcare staff as both competent and compassionate.…”
Section: Discussionsupporting
confidence: 87%
“…Interactions in the patient-nurse relationship may lead to improved self-efficacy among psychiatric nurses, because patient satisfaction is related to nurses' self-efficacy [22]. Perceived nursing care and satisfaction with care are strongly correlated in psychiatric care [23]. However, concerns have been raised that the lack…”
Section: Plos Onementioning
confidence: 99%
“…The group also experiences stigmatization, discrimination, exposure to violence and emotional suffering, and are at high risk of comorbidity and premature mortality (Goodman et al, 2001; Keyes, 2002; Khalifeh et al, 2015; Rüsch, Angermeyer, & Corrigan, 2005; World Health Organization, 2013). How they are encountered in the acute care settings is thus essential for those persons in crisis as their experiences impact on their satisfaction with care (King, Linette, Donohue‐Smith, & Wolf, 2019) and recovery processes (Waldemar, Esbensen, Korsbek, Petersen, & Arnfred, 2019). By encounters—and in line with Holopainen, Nyström, and Kasén (2019)— we refer to a “dialogue and relation describing deeper levels of interaction between patient and the [healthcare professional]” (p. 7).…”
Section: Introductionmentioning
confidence: 99%